Early mortality in multiple myeloma: Experiences from a single institution. Issue 7 (8th August 2016) - Chen, Yeh-Ku; Han, Shao-Min; Yang, Youngsen; Lin, Tseng-Hsi; Tzeng, Huey-En; Chang, Kuang-Hsi; Hwang, Wen-Li; Teng, Chieh-Lin Jerry
Abstract : Objective : Multiple myeloma (MM) is a hematological malignancy that presents with infection, anemia, bone lesions, renal function impairment, and hypercalcemia. The survival of MM patients has improved in recent decades; however, early mortality remains a critical problem. The aim of this study was to identify the etiologies and clinical variables associated with early mortality in MM. In addition, the effects of bortezomib on reducing early mortality incidence were investigated. Method and materials : Medical records from 122 MM patients diagnosed between November 2007 and December 2013 were retrospectively reviewed. Early mortality was defined as death by any cause within the first 180 days after pathological diagnosis. Results : In newly diagnosed MM patients, early mortality occurred in 22.95% of patients. Infection accounted for 67.86% of early deaths. Multivariate analyses by Cox proportional-hazards regression showed that higher β2-microglobulin ( P  < 0.001) and serum lactate dehydrogenase ( P  < 0.001) levels, and lower serum albumin levels ( P  < 0.001) were associated with early mortality. Both first-line and greater than or equal to second-line bortezomib treatments were not associated with superior 180-day overall survival ( P  = 0.546 for first-line bortezomib treatment; P  = 0.066 for greater than or equal to second-line bortezomib treatment). Conclusion : Our results suggest that infection is the leading cause of early death in MM. High β2-microglobulin, high serum lactate dehydrogenase, and low serum albumin levels are poor prognostic factors for early mortality. Bortezomib therapy does not appear to reduce the incidence of early mortality in MM patients.